2011
DOI: 10.1001/archoto.2011.8
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Obstructive Sleep Apnea in Patients With Cleft Palate

Abstract: An increased prevalence of SDB and/or OSA exists in the population with cleft palate, with an even greater prevalence in patients with Pierre Robin syndrome. Definitive diagnosis of OSA by PSG is underused. We suggest that surgical management of SDB and/or OSA be followed by PSG to demonstrate resolution or persistence of symptoms to ensure appropriate further management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 31 publications
(45 reference statements)
3
111
1
2
Order By: Relevance
“…Some of these patients were likely to have a marginal airway that was unable to tolerate the additional stress of an oral diet. Up until recently, formal polysomnography was not freely available in a timely fashion for our patients at our institution, however, it has been shown that formal polysomnography is much more sensitive at detecting marginal airways in these children [18,19]. We are likely to detect more children in the future with feeding problems that indeed have slight airway compromise just sufficient enough to warrant intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these patients were likely to have a marginal airway that was unable to tolerate the additional stress of an oral diet. Up until recently, formal polysomnography was not freely available in a timely fashion for our patients at our institution, however, it has been shown that formal polysomnography is much more sensitive at detecting marginal airways in these children [18,19]. We are likely to detect more children in the future with feeding problems that indeed have slight airway compromise just sufficient enough to warrant intervention.…”
Section: Discussionmentioning
confidence: 99%
“…e) All relevant publications are of class III or IV [30][31][32]. Not all studies concluded that repair of cleft palate increases the risk of OSAS [32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In comparison to other diseases associated with a high OSA prevalence in children, it is notable that the prevalence of OSA in children and adolescents with EDS was found to be even higher than in children and adolescents with e.g. cleft palate (8.5% with an oAHI ≥1) [22], but lower than in children with Pierre Robin syndrome (85% with a oAHI ≥1) or Down syndrome (73% with an oAHI ≥1) [23, 24]. In contrast to children suffering from these pathologies, in EDS patients craniofacial abnormalities are not risk factors for OSA [4].…”
Section: Discussionmentioning
confidence: 99%